RITUAL AS POLITICS: RAJU CULTURAL PRACTICE IN PLURAL SOCIETY OF MBAWA, WEST NUSA TENGGARA - Wahid, Abdul Wahid; Ardika, I Wayan Ardika; Mbete, Aron Meko; Mariyah, Emiliana Mariyah (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2015)
Since the New Order government the religious politics has obliged residents to adhere to one of the five official religions, causing the Mbawa society to be a plural one. They have welcome Christianity and Islam, but they still maintain their old belief, that is, Parafu. Movements have appeared in the society. The people were between peace and conflict. The last movements led to violence, taking place in 1969, 1972, and 2000. The Raju cultural practice is maintained within the context of Islamic and Christian contestations, and has been used as the arena of cultural fight. This present study discusses how the Raju ritual frees itself and its supporting people from the conflict, and how it is transformed into a means of supervising peace. The perspective of the critical theory was used in the present study to explore the texts of the Mbawa society. The discourse analysis was used to guide the discussion. Based on the fieldwork done at Mbawa from 2011 to 2014, several constructions of the Raju cultural practices were found. First, the Raju practice refers to the maintenance of identity and supremacy of the Mbawa society as conserver of the ancestor’s tradition; second, the Raju cultural practice functions as a mechanism of internal solidarity, so horizontal conflict can be avoided; and third, the Raju cultural practice plays a role as a means of revealing the “resistance” to as well as “acceptance” of the other people’s cultural domination. The finding of the study gives better understanding of the tradition-based management of conflict. It is such a character which, to some extent, has caused the Raju cultural practice to be the practice of management conflict. The significant cultural position of the Mbawa plural society could be identified from the discursive space and its potential as means of communication.